Metaphysics - Hamlyn, D. W. (Cambridge University Press, 1984)
This book provides an introduction to metaphysics. At the outset Professor Hamlyn distinguishes two conceptions of metaphysics running through the history of the subject. One, which goes back to Aristotle, is concerned with ontology, and with what has to exist for beings such as we are; the other separates appearance and reality and attempts to establish what really exists. Professor Hamlyn's account of metaphysics conforms with the first tradition. This is not, however, primarily a historical exposition. The discussion concentrates on central metaphysical concepts and problems, including the principles of ontology, substance, particulars and universals, monism and pluralism, space and time, minds, selves and personal identity. Throughout, Professor Hamlyn's thoroughly informed and argued consideration of the topics presents both a persuasive view of the subject and an excellent grounding in it.